Secure File Storage System for Disruption-Tolerant Military Environment - Amol, Pawar; Ajay, Sonawane; Pravin, Nandan; Shubham, Ingole (International Journal of Computer Sciences and Engineering, 2025)
Secure File Storage System is application to provide security to user for protect his file and also share file bin categorize we will implement some module like data storage module, data encryption module and data retrieval module and facilitate main storage and secondary storage. Now the massive quantity of expanding industrial atmosphere each and everything depends on the other sources to broadcast the data strongly and maintain the data as well in the frequent medium. Convenient nodes in military surroundings, for example, a frontage line or a hostile area are prone to experience irregular system network and common partition. Disruption-tolerant network (DTN) improvement are getting to be productive results that allow remote device get across by officers to tell with other and access the private data consistently by exploitation external capacity nodes or storage nodes. The new approach is to offer effective communication beside to another also access the different information supply through various key establishments like commander or other superiors. This system offer competent scenario for approval strategy and the strategy renew for protected data salvage in most demanding situation. The most assure cryptographic result is commenced to manage the access RSA algorithm.